Pensamento computacional, Educacao Maker e cultura digital, aplicados aos alunos do Ensino Fundamental I - Bozolan, Sandra Muniz (2021)
This is an exploratory research that aims to identify the issues that involve active methodologies in education, and how they are being used so that the protagonism of students, mediated by teachers, takes place in all learning processes. Part of the study carried out during data collection, allowed a Systematic Literature Review about active methodologies, which will be addressed in the text which allowed the organization of some of its main concepts. Of these bibliographies, some were experienced during robotics classes in 2019, where students began to experience their role in hands-on activities. From this experience, the individual's social character stands out, which is linked to the learning experience with all the variables that impact this development process. Among the approaches experienced, active methodologies, through Computational Thinking and Language Maker Education, stood out as fundamental elements in this development process, which will be analyzed through examples both from the bibliography and in real experiences lived by the researcher. This research seeks to broaden the discussion about how active methodologies, impacted by BNCC's competences and abilities, in particular Digital Culture, with particular use of computational thinking and Maker teaching, foster educational processes